Hereditary Brachydactyly Associated with Hypertension - Bilginturan, N. (1973)
A family showing brachydactyly associated with hypertension is reported. The number and location of the involved bones are quite different from the other cases with brachydactyly reported in the literature. Additionally, all our patients have high blood pressure. We believe that the disorder reported here represents a hitherto undescribed entity. It is thought that both hypertension and brachydactyly are transmitted as an autosomal dominant trait by a single pleiotropic gene or by two closely located genes.